2020
DOI: 10.1371/journal.pone.0229179
|View full text |Cite
|
Sign up to set email alerts
|

ALK inhibitors for non-small cell lung cancer: A systematic review and network meta-analysis

Abstract: Background We sought to assess the relative effects of individual anaplastic lymphoma kinase (ALK) inhibitors for the treatment of non-small cell lung cancer (NSCLC). Methods We searched MEDLINE, Embase, Cochrane CENTRAL, and grey literature (July 23, 2019) for randomized controlled trials (RCTs) that included participants with ALK-or ROS1-positive NSCLC who received any ALK inhibitor compared with placebo, another ALK inhibitor, or the same ALK inhibitor at a different dose. The primary outcome was treatment-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 45 publications
2
47
2
1
Order By: Relevance
“…Target therapy with ALK‐rearranged ADC was more effective than SCC. The duration time of treatment (our study: 6.4 ± 4.4 months) ALK‐rearranged SCC was shorter than those in previous clinical trials of ALK‐rearranged ADC studies (PROFILE1007:7.7 months, PROFILE1014:10.9 months; ALESIANCT02838420:14.6 months), 34,35 suggesting that outcomes are worse for ACC as compared to the ADC patient when ALK inhibitors are used. Therefore, ALK‐rearranged SCC patients obtained clinical benefit from ALK‐inhibitor drug treatment, but it was not as beneficial to those patients who had ALK‐rearranged ADC.…”
Section: Discussionmentioning
confidence: 54%
“…Target therapy with ALK‐rearranged ADC was more effective than SCC. The duration time of treatment (our study: 6.4 ± 4.4 months) ALK‐rearranged SCC was shorter than those in previous clinical trials of ALK‐rearranged ADC studies (PROFILE1007:7.7 months, PROFILE1014:10.9 months; ALESIANCT02838420:14.6 months), 34,35 suggesting that outcomes are worse for ACC as compared to the ADC patient when ALK inhibitors are used. Therefore, ALK‐rearranged SCC patients obtained clinical benefit from ALK‐inhibitor drug treatment, but it was not as beneficial to those patients who had ALK‐rearranged ADC.…”
Section: Discussionmentioning
confidence: 54%
“…In order to understand the efficacy and AEs of these new-generation ALKIs, several meta-analyses have been performed to identify the most beneficial ALKIs for ALK-positive lung cancer patients. For example, a recent meta-analysis showed that all ALKIs (crizotinib, ceritinib, alectinib, and brigatinib) were superior to chemotherapy in PFS, and that both alectinib and brigatinib demonstrated significantly longer PFS compared to crizotinib and ceritinib [ 26 ]. However, this network meta-analysis enrolled patients who had been treated with chemotherapy and ALKIs, which complicated the heterogeneity of the study population and hindered the application into real-world practice.…”
Section: Discussionmentioning
confidence: 99%
“…The application of tyrosine kinase inhibitors against specific gene targets (EGFR, ALK and ROS1) has revolutionized the treatment for lung adenocarcinoma ( 31 ). ALK inhibitors, such as Crizotinib and Ceritinib, have been widely used to treat cancers with mutations of ALK, especially for non-small cell lung cancers ( 32 , 33 ). For example, a small subset of lung cancer patients with rearrangements of ALK or ROS1 genes are sensitive to ALK inhibitors ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%